An Insight of Co-Encapsulation Nigella sativa and Cosmos caudatus Kunth Extracts as Anti-Inflammatory Agent Through In Silico Study - Nadiyah Zuhroh; Zubaidah Ningsih; Anna Safitri (Jurnal Kimia Sains dan Aplikasi, 2021)
This study analyzes anti-inflammatory activity from extracts of Nigella sativa and Cosmos caudatus Kunth co-encapsulated through in silico molecular docking. The LC-MS results revealed that extracts of N. sativa mostly contained thymoquinone and alpha-hederin, whereas quercetin and kaempferol were the major compounds in C. caudatus K. Nevertheless, the bioactive compounds are usually susceptible to degradation by exposure to light, heat, oxygen, which may limit its biological activity. Therefore, encapsulation is one of the promising techniques to protect bioactive compounds. Ligands were encapsulated with chitosan and sodium tripolyphosphate as wall materials. Cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2) as the target enzymes were docked with a combination of these active compounds (non-encapsulated and encapsulated), using the HEX 8.0 program, and visualized using the Discovery studio visualizer software v16.1.0.15350. Interestingly, docking results of the combination of encapsulated ligands showed no interactions to COX-1 but interacted with COX-2. Therefore, co-encapsulation of extracts combinations has been suggested to act as anti-inflammatory agents targeted specifically to the COX-2 enzyme. The total energy of the encapsulated of combination of extract compounds to COX-2 were -1425.88 (mol/cal) for thymoquinone + quercetin; -1435.87 (mol/cal) for thymoquinone + kaempferol; 1175.97 (mol/cal) for quercetin + alpha hederin; -957.74 (mol/cal) for kaempferol + alpha hederin; and -283.3 (mol/cal) for diclofenac sodium, as a control NSAID drug. These suggest that encapsulated active compounds in N. sativa and C. caudatus K. have potency as a drug candidate for the selective NSAIDs category, which can be subjected to further in vitro and in vivo studies.